The Future of Origin of Life Research: Bridging Decades-Old Divisions - Martina Preiner; Silke Asche; Sidney Becker; Holly C. Betts; Adrien Boniface; Eloi Camprubi; Kuhan Chandru; Valentina Erastova; Sriram G. Garg; Nozair Khawaja; Gladys Kostyrka; Rainer Machné; et al. (Life, 2020)
Research on the origin of life is highly heterogeneous. After a peculiar historical development, it still includes strongly opposed views which potentially hinder progress. In the 1st Interdisciplinary Origin of Life Meeting, early-career researchers gathered to explore the commonalities between theories and approaches, critical divergence points, and expectations for the future. We find that even though classical approaches and theories—e.g. bottom-up and top-down, RNA world vs. metabolism-first—have been prevalent in origin of life research, they are ceasing to be mutually exclusive and they can and should feed integrating approaches. Here we focus on pressing questions and recent developments that bridge the classical disciplines and approaches, and highlight expectations for future endeavours in origin of life research.